Management of Early and Late Malperfusion Syndrome in Acute Type B Aortic Dissection with Retrograde Extension Using Hybrid Zone 2 Arch Repair and Thoracic Endovascular Aortic Repair: A Case Report - Votano, Daniela; Beaufort, Hector W.L. de; Mortel, Rob H.W. van de; Sonker, Uday; Heijmen, Robin H.; Smeenk, Hans G. (AORTA, 2024)
The distal extent of aortic repair in acute aortic dissection and the management of malperfusion in terms of timing and strategy are still debated topics. We present a case of acute type B dissection with retrograde extension to the ascending aorta, with the most proximal intimal tear in the descending thoracic aorta, associated with both early lower extremity and delayed mesenteric malperfusion syndrome, treated effectively by femoral artery open fenestration and hybrid zone 2 arch repair.
Keywords: aortic dissection; malperfusion; hybrid arch repair